Bi-crosslinking high-strength poly-eutectic fluorescent self-repairing conductive elastomer and preparation method thereof

By introducing cysteine-modified graphene quantum dots into the eutectic conductive elastomer, forming hydrogen bonds and chemical covalent crosslinking networks, the insufficient tensile strength and low fluorescence performance of the eutectic conductive elastomer are solved. The problem of this problem is that a conductive elastomer with high strength and high fluorescence performance is achieved, and it has excellent self-healing and strain sensing performance.

CN119409859AActive Publication Date: 2025-02-11XIAN UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411166710.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-02-11
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

The tensile strength of the existing eutectic conductive elastomers is insufficient and the fluorescence performance needs to be improved, making it difficult to meet the needs of high-performance flexible sensors.

Method used

By introducing cysteine-modified graphene quantum dots (Cys-GQDs), the rich functional group sites on its surface form hydrogen bonds and chemical covalent crosslinking networks with the eutectic matrix to improve the stretching of conductive elastomers. Intensity and fluorescence properties.

Benefits of technology

The tensile strength of the eutectic conductive elastomer has been increased from 0.29MPa to 5.64MPa, the fluorescence quantum yield reaches 83.95%, and has excellent self-repair performance and strain sensing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409859A_ABST
    Figure CN119409859A_ABST
Patent Text Reader

Abstract

The invention discloses a double-crosslinking high-strength poly-eutectic fluorescent self-repairing conductive elastomer and also discloses a preparation method of the conductive elastomer, and the preparation method comprises the following steps: mixing choline chloride and acrylic acid, and then heating and stirring the mixture at 60-70 DEG C for 15-30 minutes to obtain a polymerizable eutectic solvent DES; the preparation method comprises the following steps: preparing cysteine modified graphene quantum dots (Cys-GQDs) from citric acid and cysteine; the preparation method comprises the following steps: adding Cys-GQDs and a photoinitiator into DES, and heating and stirring at 60-70 DEG C for 0.5-1 hour to obtain a prepolymer solution; and casting the prepolymer solution on a horizontal glass plate, and carrying out in-situ polymerization through ultraviolet irradiation to obtain the conductive elastomer. The conductive elastomer provided by the invention solves the problems that the tensile strength is insufficient and the fluorescence property needs to be further improved in the existing poly-eutectic conductive elastomer material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive elastic materials, and specifically relates to a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer. The present invention also relates to a preparation method of the conductive elastomer. Background Art

[0002] In recent years, with the development of soft robots, flexible electronic devices and artificial intelligence, researchers have conducted more and more research on high-performance flexible sensors, and one of its core components, flexible conductive materials, has also received more and more attention. Common flexible conductive materials mainly include two categories: hydrogels and ionic liquid gels. Among them, most hydrogels have poor temperature resistance and are difficult to work at low or high temperatures. Although ionic liquid gels have good temperature resistance, they also have problems such as high cost, complex preparation process, and poor biocompatibility. The potential risk of ionic liquid leakage has hindered its practical application. Therefore, finding a conductive elastomer with excellent comprehensive performance that is both safe and environmentally friendly is still a huge challenge.

[0003] Polyeutectic conductive elastomers are three-dimensional polymer networks formed by free radical polymerization of polymerizable monomers (commonly known as acrylic acid, acrylamide, itaconic acid and maleic acid) in high-entropy low eutectic solvents. They are highly designable, less affected by ambient temperature, and do not have the risk of organic solvent leakage. They have been favored by researchers in recent years. Although research on polyeutectic conductive elastomers has been carried out in recent years, the tensile strength of most poly (eutectic) elastomers assembled by hydrogen bonds still does not exceed 1MPa. Based on this problem, researchers doped small molecule physical crosslinkers (such as phytic acid, tannic acid, metal halide salts, graphene oxide nanosheets and MXene sheets) or polymers (such as polyethylene glycol, cellulose, polyvinyl alcohol and starch) into them, that is, by further constructing physical crosslinking networks such as hydrogen bonding and physical chain entanglement to strengthen their axial tensile mechanical behavior. However, non-chemically bonded physical enhancers will be partially analyzed in high humidity or underwater environments, so the weak bonding between them and the polyeutectic substrate and the migration problem still need to be solved. Graphene quantum dots (GQDs) are graphene sheets with a lateral size of less than 100nm. Unfunctionalized GQDs usually have low fluorescence quantum yield and poor compatibility with polymer substrates. At present, there are few studies on doping GQDs into poly-eutectic conductive elastomers. Therefore, how to reasonably design the reaction sites on the surface of modified graphene quantum dots to improve their fluorescence quantum yield while further forming a physical / chemical double cross-linked network with the poly-eutectic substrate to obtain a high-strength poly-eutectic fluorescent conductive elastomer has great research value and significance. Summary of the invention

[0004] The purpose of the present invention is to provide a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer, which solves the problems of insufficient tensile strength and the need to further improve the fluorescent performance of the current poly-eutectic conductive elastomer materials.

[0005] Another object of the present invention is to provide a method for preparing the conductive elastomer.

[0006] The technical solution adopted by the present invention is a method for preparing a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer, which is specifically implemented according to the following steps: Step 1, mixing choline chloride and acrylic acid, and then heating and stirring the mixture at 60-70° C. for 15-30 minutes to obtain a polymerizable low eutectic solvent DES; Step 2, preparing cysteine-modified graphene quantum dots Cys-GQDs using citric acid and cysteine; Step 3, adding the Cys-GQDs and photoinitiator obtained in step 2 to the DES prepared in step 1, heating and stirring at 60-70° C. for 0.5-1 h to obtain a prepolymer solution; Step 4: Cast the prepolymer solution obtained in step 3 onto a horizontal glass plate and perform in-situ polymerization by ultraviolet light irradiation to obtain a conductive elastomer.

[0007] The present invention is also characterized in that: In step 1, the molar ratio of choline chloride to acrylic acid is 1:1.8-2.4.

[0008] Step 2 is as follows: Citric acid and L-cysteine ​​were dissolved in deionized water to form a solution, and then the solution was heated at 180-220°C for 5-10 minutes. After the reaction was completed and the reaction solution was cooled to room temperature, the pH of the reaction solution was adjusted to 7, and then the reaction solution was purified using a dialysis bag. Finally, the purified solution was freeze-dried for 2-3 days to obtain cysteine-modified graphene quantum dots Cys-GQDs.

[0009] The molar ratio of citric acid to L-cysteine ​​is 1:1.

[0010] The molecular weight cut-off of the dialysis bag is 700~1000Da.

[0011] In step 3, the photoinitiator is photoinitiator 2959, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone or 2-hydroxy-2-methyl-1-phenylpropanone, and the mass of the added photoinitiator is 1% of the mass of DES.

[0012] In step 3, the mass of Cys-GQDs was 1–4% of the mass of DES.

[0013] In step 4, the wavelength of the ultraviolet light is 365 nm, the power is 40-60 W, the height of the ultraviolet lamp from the glass plate is 10-15 cm, and the irradiation time is 1-2 min.

[0014] Another technical solution adopted by the present invention is a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer, which is prepared by the above-mentioned preparation method.

[0015] The beneficial effects of the present invention are: (1) The method of the present invention designs and synthesizes cysteine-functionalized graphene quantum dots from the perspective of improving the tensile properties and self-healing properties of polyeutectic conductive elastomers. On the one hand, the rich functional group sites such as carboxyl, amino and carbonyl groups on the surface of the graphene quantum dots are used to form a rich dynamic non-covalent cross-linking network such as hydrogen bonds, acid-base pairs and cation-dipole with the polyeutectic matrix. On the other hand, the modified dithiol groups can also react with acrylic acid to form a chemical covalent cross-linking network by a "thiol-double bond" click reaction. The synergistic effect of the covalent and non-covalent double cross-linking networks increases the tensile strength of the polyeutectic conductive elastomer from 0.29 MPa to 5.64 MPa, which is 18 times higher than the tensile strength of the traditional ChCl-AA type polyeutectic conductive elastomer. (2) The raw materials used in the method of the present invention are all common commercial chemical materials, the raw material cost is low and no further chemical treatment is required. The preparation method is simple and fast, and inherits the advantages of the preparation process of the polymerizable low eutectic solvent, such as simple and efficient, green and environmentally friendly, and low energy consumption of equipment; (3) The conductive elastomer of the present invention can realize accurate signal detection in a wide temperature range (-20~60℃), a wide strain rate (100~500mm / min) and a wide strain amplitude (10%~100%), and the representative elastomer PDES-GQDs 0.04 The GF in the strain range of 10%-100% is 1.19, which is twice that of the conductive elastomer PDES without adding Cys-GQDs. In addition, the conductive elastomer of the present invention also exhibits excellent low-temperature tensile durability (more than 21,000 cycles at -20°C); (4) The cysteine-modified graphene quantum dots prepared by the method of the present invention have a fluorescence quantum yield of up to 83.95%. The prepared double-cross-linked high-strength polyeutectic fluorescent self-healing conductive elastomer and its prepolymer have good fluorescence properties. Therefore, they can be used as anti-counterfeiting "ink" and combined with screen printing technology. They can be applied to information storage and fluorescent anti-counterfeiting, which broadens the functionality of the conductive elastomer. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the principle of the method of the present invention; Figure 2This is the infrared spectrum of Cys-GQDs prepared in Example 1 of the present invention; Figure 3 XRD spectrum of Cys-GQDs prepared in Example 1 of the present invention; Figure 4 The XPS spectrum of Cys-GQDs prepared in Example 1 of the present invention, wherein ad is the overall spectrum and the XPS graphs of C, N, and S elements, respectively; Figure 5 Graph showing the fluorescence quantum yield of Cys-GQDs prepared in Example 1 of the present invention, wherein Graph a is an absorbance curve, Graph b is a fluorescence emission spectrum graph, and Graph c is a fluorescence integral area curve graph; Figure 6 The differential scanning calorimetry diagram of the DES prepared in Example 1 of the present invention; Figure 7 This is the infrared spectrum of DES prepared in Example 1 of the present invention; Figure 8 This is the hydrogen nuclear magnetic resonance spectrum of the DES prepared in Example 1 of the present invention; Fig. 9 DES, PDES and PDES-GQDs prepared in Example 4 and Comparative Example 1 of the present invention 0.04 Infrared spectrum of Fig.10 PDES-GQDs prepared in Examples 1-4 and Comparative Example 1 of the present invention x , mechanical properties comparison test chart of PDES; Fig.11 PDES-GQDs prepared in Examples 1-4 and Comparative Example 1 of the present invention x , Optical performance comparison test chart of PDES; Fig.12 PDES-GQDs prepared in Examples 1-4 and Comparative Example 1 of the present invention x , PDES thermal gravimetric performance comparison test diagram, where Figure a is the TGA curve and Figure b is the DTG curve; Fig.13 PDES-GQDs prepared in Example 4 of the present invention 0.04 Differential scanning calorimetry diagram of Fig.14 PDES-GQDs prepared in Example 4 of the present invention 0.04 Self-repair process diagram; Fig.15 PDES-GQDs prepared in Example 4 of the present invention 0.04 Electrical self-repairing performance test diagram; Fig.16 PDES-GQDs prepared in Example 4 of the present invention 0.04Electrical self-healing rate diagram; Fig.17 PDES-GQDs prepared in Examples 1-4 of the present invention x Strain sensing performance test diagram; Fig.18 PDES-GQDs prepared in Example 4 of the present invention 0.04 Relative resistance change at 5% strain amplitude and 100-300 mm / min strain speed; Fig.19 PDES-GQDs prepared in Example 4 of the present invention 0.04 Relative resistance change at 10%~100% strain amplitude and 100mm / min strain speed; Fig. 20 PDES-GQDs prepared in Example 4 of the present invention 0.04 GF value in the strain range of 10% to 100%; Fig.21 PDES-GQDs prepared in Example 4 of the present invention 0.04 Relative resistance change from -20℃ to 60℃; Fig. 22 PDES-GQDs prepared in Example 4 of the present invention 0.04 Cyclic durability test results at -20℃; Fig.23 PDES-GQDs prepared in Example 4 of the present invention 0.04 Strain sensing diagram during human action monitoring; Fig.24 PDES-GQDs prepared in Example 4 of the present invention 0.04 Application diagram in information storage and fluorescent anti-counterfeiting. DETAILED DESCRIPTION

[0017] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0018] The preparation method of the double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer of the present invention starts from the "one-pot" design principle, selects choline chloride (ChCl) and acrylic acid (AA) as hydrogen bond acceptors and hydrogen bond donors respectively, introduces cysteine-modified graphene quantum dots (Cys-GQDs) with thiol and rich polar functional groups (carboxyl, amino and carbonyl) sites as physical / chemical crosslinkers, and after in-situ polymerization and "thiol-double bond" click reaction initiated by ultraviolet light, a double-crosslinked poly-eutectic fluorescent conductive elastomer with excellent comprehensive performance is obtained. Figure 1 As shown, the method of the present invention is specifically implemented according to the following steps: Step 1: Preparation of polymerizable deep eutectic solvent (DES): Choline chloride and acrylic acid are mixed in a molar ratio of 1:1.8-2.4 to obtain a mixture, and then the mixture is heated and stirred at 60-70° C. for 15-30 minutes to obtain a uniform clear and transparent solution DES; Step 2: Preparation of cysteine-modified graphene quantum dots (Cys-GQDs): Dissolve citric acid and L-cysteine ​​in an appropriate amount of deionized water at a molar ratio of 1:1, wherein the total mass of citric acid and L-cysteine ​​is 40% to 60% of the mass of water, and then heat the mixed solution in an oil bath at 180 to 220°C for 5 to 10 minutes. After the reaction is completed and the reaction solution is cooled to room temperature, the reaction solution is neutralized with a 1 mol / L sodium hydroxide solution to a pH of 7, and then the reaction solution is purified using a dialysis bag with a molecular weight cutoff of 700 to 1000 Da. Finally, the purified solution is vacuum freeze-dried for 2 to 3 days to obtain cysteine-modified graphene quantum dots Cys-GQDs; Step 3: Preparation of prepolymer solution: Add the Cys-GQDs and photoinitiator obtained in step 2 to the clear and transparent solution DES obtained in step 1, heat and stir at 60-70° C. for 0.5-1 h to obtain a prepolymer solution; wherein the photoinitiator is photoinitiator 2959, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone or 2-hydroxy-2-methyl-1-phenylpropanone, the mass of the added photoinitiator is 1% of the mass of the solution DES, and the mass of the Cys-GQDs is 1-4% of the mass of the solution DES.

[0019] Step 4: Preparation of double cross-linked high-strength eutectic fluorescent self-healing conductive elastomer: The prepolymer solution prepared in step 3 is cast on a horizontal glass plate, and in-situ polymerized by ultraviolet light irradiation to obtain a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer. The ultraviolet light wavelength is 365nm, the power is 40-60W, the height of the ultraviolet lamp from the glass plate is 10-15cm, and the irradiation time is 1-2min.

[0020] The raw materials used in the following examples are all common commercially available products unless otherwise specified.

[0021] Choline chloride (ChCl) and acrylic acid (AA) were dried under vacuum at 60 °C for 2 h before the experiment.

[0022] Embodiment 1: Step 1: Preparation of polymerizable deep eutectic solvent (DES): Choline chloride and acrylic acid were mixed in a molar ratio of 1:2, and the mixture was placed in a flat-bottom flask and heated and stirred at 65° C. for 15 min to obtain a uniform clear and transparent solution DES. The prepared DES was stored in a vacuum desiccator containing silica gel until use in the next step.

[0023] Step 2: Preparation of cysteine-modified graphene quantum dots (Cys-GQDs): Cysteine-modified graphene quantum dots were synthesized using a high-temperature dry method. First, 10 g of citric acid and 6.306 g of L-cysteine ​​were dissolved in 30 mL of deionized water, and the mixed solution was heated in an oil bath at 200 °C for 10 min. Then, the reaction solution was neutralized with 1 mol / L sodium hydroxide solution to a pH of 7, and then the reaction solution was purified using a dialysis bag with a molecular weight cutoff of 1000 Da. Finally, the purified solution was vacuum freeze-dried for 3 days to obtain solid Cys-GQDs, which was configured into a 50 mg / mL solution for standby use.

[0024] Step 3: Preparation of prepolymer solution: The Cys-GQDs solution and the photoinitiator 2959 were added to the DES prepared in step 1, and the mixture was heated and stirred at 65°C for 30 minutes to obtain a uniform clear and transparent prepolymer solution. The amount of the photoinitiator was 1wt% of the DES, and the amount of the Cys-GQDs was 1wt% of the DES.

[0025] Step 4: Double cross-linked high-strength poly-eutectic fluorescent self-healing conductive elastomer PDES-GQDs 0.01 Preparation: The prepolymer solution prepared in step 3 was cast on a leveled glass plate and polymerized under ultraviolet light, wherein the wavelength of the ultraviolet light was 365 nm, the power was 40 W, the height of the ultraviolet lamp from the glass plate was 10 cm, and the irradiation time was 1 min to obtain a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer PDES-GQDs. 0.01 .

[0026] Embodiment 2: This example is basically the same as Example 1, except that the amount of Cys-GQDs is used. In step 3 of this example, the amount of Cys-GQDs used is 2wt% of DES, and the reaction obtains a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer PDES-GQDs. 0.02 .

[0027] Embodiment 3: This example is basically the same as Example 1, except that the amount of Cys-GQDs is used. In step 3 of this example, the amount of Cys-GQDs used is 3wt% of DES, and the reaction obtains a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer PDES-GQDs. 0.03 .

[0028] Embodiment 4: This example is basically the same as Example 1, except that the amount of Cys-GQDs is used. In step 3 of this example, the amount of Cys-GQDs used is 4wt% of DES, and the reaction obtains a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer PDES-GQDs. 0.04 .

[0029] Embodiment 5: Step 1: Mix choline chloride and acrylic acid in a molar ratio of 1:1.8, place the mixture in a flat-bottom flask and heat and stir at 70° C. for 20 min to obtain a uniform clear and transparent solution DES, and store the prepared DES in a vacuum desiccator containing silica gel until use in the next step.

[0030] Step 2: Synthesize cysteine-modified graphene quantum dots using a high-temperature dry method. First, dissolve 10 g of citric acid and 6.306 g of L-cysteine ​​in 40 mL of deionized water. Heat the mixed solution in an oil bath at 220 °C for 5 min. Then, neutralize the reaction solution with 1 mol / L sodium hydroxide solution to a pH of 7. Then, purify the reaction solution using a dialysis bag with a molecular weight cutoff of 800 Da. Finally, freeze-dry the purified solution in a vacuum freeze-drying process for 2 days to obtain solid Cys-GQDs, which are configured into a 50 mg / mL solution for standby use.

[0031] Step 3: Add the Cys-GQDs solution and the photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone to the DES prepared in step 1, and heat and stir the mixture at 70°C for 1 hour to obtain a uniform, clear and transparent prepolymer solution. The amount of the photoinitiator is 1wt% of the DES, and the amount of the Cys-GQDs is 1wt% of the DES.

[0032] Step 4: cast the prepolymer solution obtained in step 3 onto a leveled glass plate, and polymerize under ultraviolet light, wherein the wavelength of the ultraviolet light is 365 nm, the power is 50 W, the height of the ultraviolet lamp from the glass plate is 15 cm, and the irradiation time is 2 min to obtain a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer PDES-GQDs.

[0033] Embodiment 6: Step 1: Mix choline chloride and acrylic acid in a molar ratio of 1:2.4, place the mixture in a flat-bottom flask and heat and stir at 60° C. for 30 minutes to obtain a uniform clear and transparent solution DES, and store the prepared DES in a vacuum desiccator containing silica gel until use in the next step.

[0034] Step 2: Synthesize cysteine-modified graphene quantum dots using a high-temperature dry method. First, dissolve 10 g of citric acid and 6.306 g of L-cysteine ​​in 50 mL of deionized water. Heat the mixed solution in an oil bath at 180 °C for 8 min. Then, neutralize the reaction solution with 1 mol / L sodium hydroxide solution to a pH of 7. Then, purify the reaction solution using a dialysis bag with a molecular weight cutoff of 700 Da. Finally, freeze-dry the purified solution in a vacuum freeze-drying process for 3 days to obtain solid Cys-GQDs, which are configured into a 50 mg / mL solution for standby use.

[0035] Step 3: Add the Cys-GQDs solution and the photoinitiator 1-hydroxycyclohexyl phenyl ketone to the DES prepared in step 1, and heat and stir the mixture at 60° C. for 1 hour to obtain a uniform, clear, transparent prepolymer solution. The amount of the photoinitiator is 1wt% of the DES, and the amount of the Cys-GQDs is 1wt% of the DES.

[0036] Step 4: cast the prepolymer solution obtained in step 3 onto a leveled glass plate, and polymerize under ultraviolet light, wherein the wavelength of the ultraviolet light is 365 nm, the power is 60 W, the height of the ultraviolet lamp from the glass plate is 15 cm, and the irradiation time is 2 min to obtain a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer PDES-GQDs.

[0037] Comparative Example 1: In this comparative example, Cys-GQDs were not added, and the rest was the same as in Example 1, and the polyeutectic conductive elastomer PDES was obtained by reaction.

[0038] The following performance tests were performed on various substances prepared in the examples and comparative examples: (1) Fourier-transform infrared spectroscopy (FT-IR): Thermo Scientific Nicolet iS20 Fourier-transform infrared spectrometer produced by Thermo Fisher Scientific was used to measure the characteristic parameters such as wave number, intensity and shape of functional groups in the molecular structure. The scanning range was 4000~400cm -1 , resolution 16cm -1 , the number of scans is 32.

[0039] (2) H NMR spectroscopy ( 1H-Nuclear magnetic resonance, 1 H-NMR: A nuclear magnetic resonance spectrometer (Bruker 400M) produced by Bruker Instruments of Germany was used to measure the chemical shift of protons in the molecular structure and characteristic peak areas and other characteristic parameters. According to the polarity of the test molecule, a suitable deuterated reagent was selected, using deuterated dimethyl sulfoxide (DMSO- d 6) The single peak at 2.50 ppm is the standard reference peak.

[0040] (3) X-ray diffraction (XRD): The crystal phase of the samples was analyzed using an X-ray diffractometer (Rigaku SmartLabSE, Japan) with Cu-Ka rays as the incident light source, an acceleration voltage of 40 kV, a scanning angle of 5°~80°, and a scanning speed of 5° / min.

[0041] (4) X-ray photoelectron spectroscopy (XPS): The surface charge of the sample was obtained using an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha). The sample was cut into 5 × 5 mm 2 The sample of different sizes is attached to the sample plate and placed in the sample chamber of the Thermo Scientific K-Alpha XPS instrument. The pressure in the sample chamber is less than 2.0×10 -7 When the pressure was 0.1377 W / mbar, the sample was sent into the analysis chamber, and monochromatic AlKa rays with 1486.6 eV photons were used as the excitation source, with a spot size of 400 μm, an operating voltage of 12 kV, and a filament current of 6 mA. The full spectrum scan energy was 150 eV with a step size of 1 eV, and the narrow spectrum scan energy was 50 eV with a step size of 0.1 eV.

[0042] (5) Fluorescence quantum yield (FLQY): Quinine sulfate with a similar wavelength range was selected as a reference, and the slope method was used to determine the fluorescence quantum yield of Cys-GQDs. The fluorescence quantum yield of quinine sulfate under the excitation wavelength of 360 nm was 0.54. The specific operation was as follows: Quinine sulfate was dissolved in 0.1 mol / L H2SO4 to prepare solutions of different concentrations, and its absorbance was measured to make it less than 0.1. Similarly, Cys-GQDs were prepared into dispersions of different concentrations, and its fluorescence spectrum was measured to make its absorbance close to the absorbance measured at each concentration of quinine sulfate. Then, with 360 nm as the excitation wavelength, the fluorescence spectra of each sample with the corresponding concentration of each absorbance value were measured, and the emission peak area of ​​each fluorescence spectrum was calculated by integration. A graph was drawn with the absorbance of quinine sulfate and each graphene quantum dot as the horizontal axis and the fluorescence peak area as the vertical axis. The fluorescence quantum yield of each graphene quantum dot was calculated using the following formula.

[0043]

[0044] Among them, Y and Y r are the fluorescence quantum yields of each analyte and reference substance quinine sulfate, m s and m r are the ratios (slopes) of the integrated fluorescence peak areas of each analyte and reference to the absorbance; n s and n r is the refractive index of each analyte and quinine sulfate solution, which is generally 1.33.

[0045] (6) Thermal properties: The thermal stability of the conductive elastomer was measured using a TG 209F3 thermogravimetric analyzer (NETZSCH Instrument Manufacturing Co., Ltd., Germany) with a temperature range of 100-800°C and a heating rate of 20°C / min. The entire heating process was carried out under N2 protection. The melting point of the low eutectic solvent was measured using a DSC 200F3 differential scanning calorimeter (NETZSCH Instrument Manufacturing Co., Ltd., Germany). The test atmosphere was N2, the heating and cooling rate was 10°C / min, and the total temperature test range was -80°C to 90°C.

[0046] (7) Optical properties: The optical transmittance and absorptivity of the conductive elastomer were obtained by using an ultraviolet spectrophotometer (V-700).

[0047] (8) Mechanical properties: The mechanical properties of the composite film were tested using an AI-7000-NGD electronic universal testing machine (Gottwell (Dongguan) Co., Ltd.). The self-healing efficiency was characterized by the ratio of the tensile area of ​​the self-healed sample to the original sample. The self-healing temperature was room temperature, the self-healing time was 24 h, and the sample rectangular size was 40 × 10 mm. 2 , the loading rate is 100mm / min.

[0048] (9) Resistance-time signal measurement: In the experiment, an electrochemical workstation (CHI660E) was used to measure the electrical signal changes of the conductive elastomer, and the it mode was selected for measurement. The test environment temperature was 25°C and the relative humidity was 30%~35%.

[0049] (10) Optical image capture: Use a camera to capture an optical image of the conductive elastomer.

[0050] The test results are as follows: (1) The test results of Cys-GQDs prepared in Example 1 are as follows: In order to characterize the successful synthesis of cysteine-modified graphene quantum dots, FT-IR spectroscopy was used to characterize the chemical structure of the product. Figure 2 The infrared spectra of citric acid, cysteine ​​and Cys-GQDs are shown. It can be seen that the FT-IR spectrum of Cys-GQDs has a peak at 3548 cm -1 and 3440cm -1 The stretching vibration peak of -OH and the asymmetric stretching vibration peak of -NH2 appeared at 2547 cm -1 The peak at 1586 cm is attributed to the stretching vibration of -SH. -1 and 1706cm -1 The peaks at 1074 cm-1 are attributed to the -C=O stretching vibration of the carboxylic acid and amide bonds, respectively. -1 and 1398cm -1 The characteristic absorption peaks of -COC and -C-NH-C are shown at the positions, and the successful grafting of functional groups such as thiol and amino groups indicates the successful preparation of cysteine-modified quantum dots. Figure 3 ) It can be seen that Cys-GQDs has a broad diffraction peak at 2θ=23°, corresponding to an interlayer spacing of 0.385nm, which indicates that Cys-GQDs have a disordered graphene structure, which is slightly larger than the interlayer spacing of 0.335nm of original graphene. This is also due to the presence of many functional groups on its surface, further proving the presence of rich functional groups on the surface of quantum dots. In order to further study the surface chemistry of Cys-GQDs, XPS spectroscopy was used to characterize the types of elements and the chemical environment of each element, such as Figure 4 As shown in a, the XPS spectrum of Cys-GQDs shows four peaks at 163, 284.38, 399.56 and 531.22 eV, corresponding to the four elements C, O, N and S, respectively, which indicates that Cys-GQDs are composed of these four elements. 1s The XPS graph also shows three peaks at 284.31, 285.62 and 287.75 eV ( Figure 4b), which are respectively attributed to C=C, CO / CS / CN and C=O bonds; N 1s The XPS graph of has two obvious peaks at 399.00 and 399.65 eV, which are attributed to pyridinic nitrogen and pyrrolic nitrogen, respectively. Figure 4 c); S 2p The XPS graph shows two peaks at 162.84 and 164.03 eV ( Figure 4 d), proving the existence of CSC groups. The above results further prove that Cys-GQDs have been successfully prepared. The luminescence performance of fluorescent materials is usually evaluated by fluorescence quantum yield. A high fluorescence quantum yield indicates a high luminescence efficiency. Figure 5 a shows the absorbance curves of different concentrations of quinine sulfate and Cys-GQDs. Figure 5 The fluorescence emission spectra of quinine sulfate and Cys-GQDs with different absorbances are given in b, and then Figure 5 The fluorescence integrated area curve at different absorbances shown in c shows that the fluorescence quantum yield of Cys-GQDs is 83.95% calculated from the slope of the curve.

[0051] (2) The test results of the DES prepared in Example 1 are as follows: like Figure 6 As shown in Figure 2, the melting point of DES was determined to be -7.6 °C by differential scanning calorimetry, which is lower than that of its component ChCl (T m =305℃) and AA (T m =14℃) melting point, directly proving the successful synthesis of DES. The chemical structure of DES was analyzed using FT-IR spectroscopy, such as Figure 7 As shown, except for 1481cm -1 and 1087cm -1 The peak corresponds to the bending vibration peak of -CH2 in choline chloride and CN + In addition to the asymmetric stretching vibration peak at 1722 cm -1 The stretching vibration peak of C=O of the carboxyl group in the acrylic acid component was observed at 2680 cm-1, proving that it still exists in the form of carboxylic acid rather than molten salt, indicating that DES is connected by hydrogen bonds; -1 and 3660cm -1 The wide band between corresponds to the stretching vibration peak of the OH bond, which also verifies the above inference. 1 H-NMR spectrum ( Figure 8 ), the chemical shifts and integral ratios of the characteristic peaks of all characteristic protons match well with those of ChCl and AA, and the continuous shift to low field further confirms the formation of hydrogen bonds in DES.

[0052] (3) Conductive elastomer PDES-GQDs prepared in Example 4 0.04 The infrared characterization test results of the conductive elastomer PDES prepared in Comparative Example 1 are as follows: like Fig. 9 As shown in a, in the PDES elastomer without the introduction of Cys-GQDs, after in situ photopolymerization, the 1427 cm -1 C=C and 951cm -1 =CH-related stretching vibration peaks are significantly weakened, and the peak of PAA at 1719 cm -1 The carboxyl group at the position remains intact and after polymerization, the red shift is to 1717 cm -1 ( Fig. 9 b), indicating successful polymerization. After the introduction of Cys-GQDs, the -1 The stretching vibration peak belonging to the thiol group in Cys-GQDs was significantly reduced, indicating that the thiol group on Cys-GQDs and the olefin on the acrylic acid in DES successfully underwent a "thiol-double bond" click reaction.

[0053] (4) Conductive elastomer PDES-GQDs prepared in Examples 1-4 x The comparative test results of the mechanical properties, optical transmittance and thermal properties of the conductive elastomer PDES prepared in Comparative Example 1 are as follows: The mechanical properties of the double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer prepared by the present invention are as follows: Fig.10 As shown in the figure, as the Cys-GQDs content gradually increases from 0wt% to 4wt%, the strain of the conductive elastomer decreases from the initial 1200% to 525%, and the elastomer PDES-GQDs x The strength of PDES-GQDs increased from 0.29MPa to 5.64MPa. 0.04 The strength of the sample is 19.4 times that of the blank sample. This is because the introduction of Cys-GQDs further enriches the hydrogen bond density in the conductive elastomer, and the thiol groups on the quantum dots and the double bonds on the acrylic acid monomers successfully undergo a "thiol-double bond" click reaction. The chemical and physical double cross-linked network has greatly improved its mechanical strength. In addition, although the introduction of Cys-GQDs during the polymerization process will react with the double bonds on the acrylic acid in DES to generate new carbon-sulfur covalent bonds, thereby affecting the optical transmittance of the conductive elastomer, the conductive elastomer still has good optical transmittance when 4wt% of Cys-GQDs are added in the experiment. The PDES-GQDs were quantified using a UV / visible spectrophotometer. 0.04 The optical transmittance in the visible light range is still greater than 60% ( Fig.11 ). Using TGA ( Fig.12 a) and DTG curve ( Fig.12 b) The thermal properties of the samples were tested at a heating rate of 20 °C / min in a N2 atmosphere. In the temperature range of 100~700 °C, the pre-dried PDES and PDES-GQDs x The elastomer exhibits a typical two-step degradation when heated. The first step of thermal degradation occurs at 170-280°C, which is caused by the decarboxylation of the carboxyl groups in the polyacrylic acid component. The second step of thermal decomposition occurs at 280-500°C ( Fig.12 b), which is due to the decomposition of CC bonds in PAA and ChCl components. After adding Cys-GQDs, PDES-GQDs 0.04 The first-order initial degradation temperature of the elastomer was 20°C higher than that of the control PDES elastomer, and the weight loss was reduced by 7%. This result can be attributed to the formation of non-covalent interactions such as high-density hydrogen bonds and cation dipoles between Cys-GQDs and the low eutectic solvent. In addition, in the presence of Cys-GQDs, the initial thermal degradation temperature of the second stage increased by 70°C, which confirmed that a "thiol-double bond" click reaction occurred after the introduction of Cys-GQDs, and new carbon-sulfur covalent bonds were generated. In addition, differential scanning calorimetry was used to measure the PDES-GQDs in the range of -100~80°C. 0.04 Thermal behavior of elastomers. PDES-GQDs 0.04 There is no obvious crystallization peak in the DSC curve of the elastomer ( Fig.13 ), and its glass transition temperature is -23.17℃, showing an amorphous structure and good low temperature resistance.

[0054] (5) Conductive elastomer PDES-GQDs prepared in Examples 1-4 x The test results of the self-healing performance, fluorescence performance and strain sensing performance are as follows: The double cross-linked high-strength poly-eutectic fluorescent self-healing conductive elastomer prepared by the present invention also has excellent self-healing performance and fluorescence performance. Its fluorescence phenomenon can be clearly observed under 365nm ultraviolet light. Use a blade to cut two pieces of conductive elastomer evenly, and then splice the two flat sections together under mild pressure. When a certain force is manually applied and stretched to 100% deformation, it will not break, and it can still return to its original shape after the force is removed, indicating its excellent room temperature self-healing performance ( Fig.14 ); At the same time, in order to characterize the electrical self-healing properties of the conductive elastomer, a small light bulb was used for intuitive detection ( Fig.15 ), after being cut off, the small bulb turns from bright to dark, and after being spliced ​​again, the electrical properties can be quickly restored to make the bulb glow, indicating its excellent room temperature electrical self-repair performance. Fig.16As shown, in order to accurately measure the electrical self-healing rate, the IT mode of the electrochemical workstation was used to track the current in real time. The results showed that once the two fracture interfaces came into contact, the PDES-GQDs 0.04 The elastomer quickly recovered from 0A to the original current signal within 0.04s.

[0055] The double-crosslinked high-strength polyeutectic fluorescent self-healing conductive elastomer prepared by the present invention has excellent strain sensing performance. 0.04 Good mechanical properties, electrical self-healing and conductive properties of elastomers using PDES-GQDs 0.04 The elastic body is assembled with high performance strain sensors. Fig.17 As shown in Figure 2, at a strain rate of 100 mm / min and a strain amplitude of 5%, PDES-GQDs 0.04 The relative resistance change (ΔR / R0) value of the sensor increases with the increase of the amount of Cys-GQDs added, showing a linear growth trend overall. In particular, when the Cys-GQDs content reaches 4wt%, the relative resistance change reaches the highest, which is about twice that of the PDES elastomer, which also shows that the addition of Cys-GQDs improves the response sensitivity of the strain sensor. Fig.18 As shown, the elastic PDES-GQDs were further observed under a fixed strain of 5%. 0.04 The relative resistance change value is almost unchanged at different stretching speeds of 100~300mm / min, except for the rebound hysteresis phenomenon at 300mm / min. At the stretching speed of 400mm / min and above, the response of the strain sensor is slightly reduced, which proves the response stability of the elastomer under high-speed strain (200mm / min). In the practical application of strain sensors assembled with elastomers, they are often significantly affected by their sensitivity to small strains. In order to characterize the sensitivity of the elastomer to strain, the elastomer PDES-GQDs was tested at a strain rate of 100mm / min. 0.04 The assembled strain sensor was tested for its response in the strain range of 10% to 100%. The results showed that its ΔR / R0 value gradually increased ( Fig.19 The sensitivity of the tensile strain sensor was evaluated using the strain sensitivity factor (GF), which is defined as the rate of change of resistance with applied strain. Fig. 20 As shown, PDES-GQDs 0.04 The GF value in the strain range of 10% to 100% is 1.19, which is more than twice that of PDES. This should be attributed to the 0.04 The Cys-GQDs component introduced into the elastomer has good conductivity. Fig.21 It can be seen that at temperatures of -20°C and 60°C, PDES-GQDs 0.04The relative resistance change of the elastomer is close to that at 25°C, indicating that it has high and low temperature resistant sensing performance. Considering the outstanding low temperature tolerance mentioned above, the PDES-GQDs 0.04 Cyclic durability of the elastomer sensor at -20°C with a strain rate of 100 mm / min and a strain amplitude of 3%. Fig. 22 The results show that PDES-GQDs have a fast and stable response in the stretching cycle, and the residual strain after 21000 cycles is negligible, indicating that 0.04 Elastomers have remarkable low temperature fatigue sensing properties.

[0056] The conductive elastomer prepared by the present invention is used in human motion monitoring. Fig.23 As shown, the elastomer PDES-GQDs 0.04 Captured the frown ( Fig.23 a) and mouth opening and closing ( Fig.23 b) and other micro-expressions or facial movements related to tension changes, which lays the foundation for designing facial recognition technology in combination with human-computer interaction. In addition to detecting small facial movements, PDES-GQDs 0.04 When elastic bodies are assembled at different joints of the human body, they can also sense other larger-scale human movements and motions. For example, tracking the nodding of the head at the neck joint ( Fig.23 c), finger joint bending ( Fig.23 d), wrist joint hand up and down movement ( Fig.23 e), elbow joint arm bending ( Fig.23 f), knee and ankle walking ( Fig.23 g and Fig.23 i) and chest expansion exercises ( Fig.23 h), the corresponding regular ΔR / R0 values ​​and similar electrical signal curves are obtained. In particular, Fig.23 As shown in Figure c, the bending angle of the neck can be determined by the change in the relative resistance of the elastic body. When it is made into a wearable device, the ΔR / R0 generated by bending at a certain angle is set as the warning line. Once the warning line is exceeded for a long time, a reminder will be issued, which ultimately plays a role in intelligently protecting the health of the user. In general, these results highlight that PDES-GQDs 0.04 Wearable strain sensors assembled from elastomers effectively collect somatosensory motion signals from different body regions, have consistent real-time reproducibility and stability, and have the potential to be made into smart wearable devices, or may provide new inspiration for the improvement of flexible electronic devices.

[0057] In addition, given the conductive elastomer PDES-GQDs x Possessing good fluorescence performance and strain sensing performance, Fig.24 The application of its prepolymer in fluorescent anti-counterfeiting performance and tampering display function. Fig.24 As shown in the figure, since Cys-GQDs have good fluorescence properties, conductive elastomer prepolymer is used as ink for screen printing, and coated paper is selected as the substrate. In order to enrich its application in information storage and anti-counterfeiting, a barcode and QR code with embedded information XAUT are designed ( Fig.24 a) and screen printed to obtain Fig.24 As shown in b, good fluorescent anti-counterfeiting can still be performed even after drying and curing. At the same time, the results also show that the QR code recognition effect is stronger than the barcode, which is attributed to the richer information in the QR code and easier positioning during recognition.

Claims

1. A method for preparing a double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer, characterized in that: Follow the steps below to implement it: Step 1, mixing choline chloride and acrylic acid, and then heating and stirring the mixture at 60-70° C. for 15-30 minutes to obtain a polymerizable low eutectic solvent DES; Step 2, preparing cysteine-modified graphene quantum dots Cys-GQDs using citric acid and cysteine; Step 3, adding the Cys-GQDs and photoinitiator obtained in step 2 to the DES prepared in step 1, heating and stirring at 60-70° C. for 0.5-1 h to obtain a prepolymer solution; Step 4: Cast the prepolymer solution obtained in step 3 onto a horizontal glass plate and perform in-situ polymerization by ultraviolet light irradiation to obtain a conductive elastomer.

2. The method for preparing the double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer according to claim 1, characterized in that: In step 1, the molar ratio of choline chloride to acrylic acid is 1:1.8-2.

4.

3. The method for preparing the double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer according to claim 1, characterized in that: Step 2 is as follows: Citric acid and L-cysteine ​​were dissolved in deionized water to form a solution, and then the solution was heated at 180-220°C for 5-10 minutes. After the reaction was completed and the reaction solution was cooled to room temperature, the pH of the reaction solution was adjusted to 7, and then the reaction solution was purified using a dialysis bag. Finally, the purified solution was freeze-dried for 2-3 days to obtain cysteine-modified graphene quantum dots Cys-GQDs.

4. The method for preparing the double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer according to claim 3, characterized in that: The molar ratio of the citric acid to L-cysteine ​​is 1:

1.

5. The method for preparing the double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer according to claim 3, characterized in that: The molecular weight cut-off of the dialysis bag is 700-1000Da.

6. The method for preparing the double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer according to claim 1, characterized in that: In step 3, the photoinitiator is photoinitiator 2959, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone or 2-hydroxy-2-methyl-1-phenylpropanone, and the mass of the added photoinitiator is 1% of the mass of DES.

7. The method for preparing the double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer according to claim 1, characterized in that: In step 3, the mass of Cys-GQDs was 1–4% of the mass of DES.

8. The method for preparing the double-crosslinked high-strength poly-eutectic fluorescent self-healing conductive elastomer according to claim 1, characterized in that: In step 4, the wavelength of the ultraviolet light is 365 nm, the power is 40-60 W, the height of the ultraviolet lamp from the glass plate is 10-15 cm, and the irradiation time is 1-2 min.

9. Double cross-linked high-strength poly-eutectic fluorescent self-healing conductive elastomer, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for forming nitrogen and sulfur co-doped graphene quantum dots

    CN104812697A

  • Method for detecting content of pirimicarb in food by combining sulfur-doped carbon quantum dots with enzyme inhibition method

    CN113189073A

  • High-transparency self-repairing self-adhesion conductive elastic material and preparation method thereof

    CN114262403A

  • Method for auxiliary synthesis of fluorescent probe by deep eutectic solvent and application

    CN114891502A

  • Preparation method and application of MXene-poly eutectic base conductive elastomer

    CN116515038A